Prisms to Shift Pain Away: Pathophysiological and Therapeutic Exploration of CRPS with Prism Adaptation - Laure Christophe; Eric Chabanat; Ludovic Delporte; Patrice Revol; Pierre Volckmann; Sophie Jacquin-Courtois; Yves Rossetti (Neural Plasticity)
Complex Regional Pain Syndrome (CRPS) is an invalidating chronic condition subsequent to peripheral lesions. There is growing consensus for a central contribution to CRPS. However, the nature of this central body representation disorder is increasingly debated. Although it has been repeatedly argued that CRPS results in motor neglect of the affected side, visual egocentric reference frame was found to be deviated toward the pain, that is, neglect of the healthy side. Accordingly, prism adaptation has been successfully used to normalize this deviation. This study aimed at clarifying whether 7 CRPS patients exhibited neglect as well as exploring the pathophysiological mechanisms of this manifestation and of the therapeutic effects of prism adaptation. Pain and quality of life, egocentric reference frames (visual and proprioceptive straight-ahead), and neglect tests (line bisection, kinematic analyses of motor neglect and motor extinction) were repeatedly assessed prior to, during, and following a one-week intense prism adaptation intervention. First, our results provide no support for visual and motor neglect in CRPS. Second, reference frames for body representations were not systematically deviated. Third, intensive prism adaptation intervention durably ameliorated pain and quality of life. As for spatial neglect, understanding the therapeutic effects of prism adaptation deserves further investigations.